Atractylenolide I inhibits EMT and enhances the antitumor effect of cabozantinib in prostate cancer via targeting Hsp27 - Qiao, Pengfei; Tian, Zhentao (Frontiers in Oncology, 2023)
Abstract Objective: To investigate the effect of Hsp27 and the inhibitory effect of Atractylenolide I (ATL-1) on the proliferation of prostate cancer cell DU145 and PC-3. Methods: MTT assay was used to detect the inhibitory effect of silencing Hsp27 and ATL-1 on DU145 and PC-3 proliferation of prostate cancer cells. TUNEL detected the apoptosis rate of prostate cancer cell DU145 and PC-3 after silencing Hsp27 and ATL-1 treated. qRT-PCR was used to detect the changes of apoptosis related genes caspase-3, PARP, Bax and Bcl-2 in prostate cancer cell DU145 and PC-3 after the effect of silencing Hsp27 and ATL-1 treated. At the same time, the antitumor effect of ATL-1 combined with cabozantinib was analyzed. Results: Hsp27 was highly expressed in human prostate cancer. MTT assay showed that ATL-1 inhibited the proliferation of prostate cancer cells DU145 and PC-3 compared with the control group. TUNEL results showed that silencing Hsp27 and ATL-1 treated could significantly promote the apoptosis of prostate cancer cells DU145 and PC-3 compared with the control group. qRT-PCR results showed that compared with the control group, ATL-1 could promote the expression of caspase-3, PARP and Bax in DU145 and PC-3 prostate cancer cells. Inhibition of Hsp27 by ATL-1 reduced cell viability and induced apoptosis. ATL-1 inhibits the antitumor effect of Hsp27 - enhanced cabozantinib. Hsp27 regulates eIF4E and mediates cell protection. Conclusion: Silencing Hsp27 inhibits EMT. ATL-1 can inhibit the malignant evolution of prostate cancer cells by inhibiting Hsp27/eIF4E axis. ATL-1 also enhanced chemosensitization of cabozantinib in prostate cancer.